PENGARUH LAMA TERESAN DAN DIAMETER TEGAKAN JATI TERHADAP PERSENTASE KERUSAKAN KAYU - Soenamo Soenamo; Marnan Mansyur Idris (Jurnal Penelitian Hasil Hutan, 1990)
Girdling  treatment  of  teak  stand  before  felling  not  only  intended to reduce  the teak  wood  damage  but also aimed at reducing  log  transport costs. On  the  other hand,  prolonged girdling  treatment could generate significant disadvantage effect, among others:  decreasing total  wood  volume,  degrade  forest land fertility, and often  inducing  wild under growth, etc.This study  deals  with a  research  on  the  extent  of  the  effect of girdling and size of diameter  on the  logging damages.            The study  was  carried  out at Pasar Sore  Sub  Forest District, at  Cepu, Central  Java. This study reveals that  the extent of  the damages are inversely proportional to the girdling time  and diameter  of  the trees.            The average damage  percentages  per trees  on one  year girlding duration with  diameter  classes 50 -59 cm,  60 - 69 cm, 70 -79 cm  are 3.02 %, 4.17% and  7.41%,  while  on  the  two  years  girdling  duration   the  damage  for  the  same diameter classes are 5.62   %,  6.76 % and  7.08%,  respectively.